“ Stories for adults” four stories from blue - Wijewardene, Shermal (University of Colombo, 2011)
This paper presents a literary analysis of Blue 6UL /DQND¶V ILUVW (QJOLVK ODQJXDJH anthology of erotica that publicly went on sale in January 2011. It specifically examines the collection for four stories of eroticism between women. The main question focuses on the subtitle of Blue ZKLFKIUDPHVWKHFRQWHQWVRIWKHFROOHFWLRQDV³VWRULHVIRUDGXOWV ´7KH SDSHU DVNV KRZLWLV SRVVLEOHWR UHDGWKHVH IRXU VWRULHV RI GHVLUH DV ³VWRULHV IRU DGXOWV´ given that in the wider socio-political context, the expression of desire between adult women, in public or in private, and whether consenting or not, is interpreted to be criminalized in Sri Lanka due to the existence of Section 365A of the Penal Code. It DGGUHVVHVWKLVTXHVWLRQIURPWKHSHUVSHFWLYHRIWKHQRWLRQRI³VH[XDOFLWL]HQVKLS´ZKLFKLV WKHYLHZWKDWDQLQGLYLGXDO¶VVWDQGLQJ LQWHUPVRIKRZKHRUVKHLVSRVLWLRQHGDVDFLWL]HQ is affected by his or her sexuality, specifically in relation to the enjoyment of civil, political, social, and cultural rights (Richardson, 1998). Of particular relevance to this viewpoint is the idea that citizenship norms, particularly as they are constituted by these rights, are structured by heterosexuality²specifically certain dominant models of heterosexuality (Richardson, 2000). Thus, the paper claims that these four stories prompt us to consider what it means for a text such as Blue to include stories to do with same-sex desiring women in Sri Lanka as ³VWRULHV IRUDGXOWV´ ZKHQWKRVH VXEMHFWVDQGWKHH[SUHVVLRQRIWKHLUGHVLUHVDppear to be H[FOXGHG IURP WKH IUDPHZRUNV RI FLWL]HQVKLS ,V ³VWRULHV IRU DGXOWV´ D PLVOHDGLQJ description? Or is it an illustration of how Blue, as a cultural text, invokes cultural rights, one of the axes of citizenship? In other words, is it a bold articulation of the cultural rights of these subjects and their desires, in terms of assigning them representation, visibility, DQG OHJLWLPDF\" %\ FXOWXUDO ULJKWV WKLV SDSHU UHIHUVWR ³WKH ULJKW WR V\PEROLF SUHVHQFH dignifying representation, propagation of iGHQWLW\DQGPDLQWHQDQFHRIOLIHVW\OHV´ 3DNXOVNL 1997, p. 73). It asks if the subtitle, instead of being a mere description, actually hails each of the four stories as a legitimate cultural narrative of love in Sri Lanka. The paper is premised on the assumption, developed by the scholarly analysis of sexual stories and 19 storytelling, that the sexual stories told by the members of a given society can powerfully define their culture (Plummer, 1995). Arguing that Blue in fact does hail the stories in this way, the paper explores the question of the significance of a text like Blue for the wider intellectual and other engagements on gender and sexuality in Sri Lanka. The paper begins by examining the tensions between the subtitle, the four stories, and the socio-cultural contexts of the production of Blue. It DFNQRZOHGJHV WKH PXOWLSOH PHDQLQJV RI ³VWRULHV IRU DGXOWV´ LQFOXGLQJ WKH VHHPLQJO\ DEVXUG \HWSURGXFWLYH LGHDRI³DGXOW´UDWLQJLPSOLHGE\WKH IRXUVWRULHV ,WVFRQFOXVLRQV DUH WKDW ³VWRULHV IRU DGXOWV´ hails these four stories at multiple levels, chiefly that such stories should be published for adult reading, in full recognition of the contradictions implied by Sri Lankan social contexts; that sexualities²complex, multiple, forbidden, permitted etc.²caQ EHDWWDFKHGWR DQG µSDVV¶ XQGHUWKH VHHPLQJO\LQQRFXRXVLGHQWLW\ RI ³DGXOW´LQVWHDGRIPRUHVRFLDOO\SUREOHPDWLFDSSHOODWLRQV DQGWKDWLQHDFKRIWKHVWRULHV ³DGXOW´LV SURGXFHG DQGPDLQWDLQHG DV D ERXQGDU\WKDW KDVLPSOLFDWLRQV IRUWKHZD\VLQ which tKHFROOHFWLRQ DVDZKROH VXPPRQVWKHQDUUDWLYHVDQGSUHVHQWVDV³DOLWWOHERRNRI 6UL/DQNDQHURWLFD´